Nonatherosclerotic Vasculopathies Have Distinct Characteristics - Nichols, Emma Hitt (MD Conference Express, 2014)
Multiple vasculopathies other than atherosclerosis can cause the narrowing or occlusion of arteries, and while they have some overlapping symptoms, they also have distinct characteristics that providers should use to reach a differential diagnosis. This article discusses Moyamoya disease, reversible cerebral vasoconstriction syndromes, and central nervous system vasculitis.